Intern’s knowledge of clinical pharmacology and therapeutics at Puducherry: a cross-sectional study - S, Nitya; A, Mangaiarkkarasi; R, Meher Ali; Sawadkar, Maruthi Sripathi (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Internship is the intermediate period between under-graduation and general practice. The dexterity of health professional relies upon prescribing practices. Clinical pharmacology and therapeutics (CPT) is a crucial discipline for interns to acquire safe and rational prescription of drugs. Cultivating sound knowledge about CPT during under graduation is, henceforth, mandatory. Aims and objectives: To assess whether the undergraduate CPT teaching and internship training had prepared interns adequately for safe and rational prescription. To assess the awareness and reporting of adverse drug reaction (ADR). Methods: 110 interns were enrolled after obtaining informed written consent. A structured questionnaire was given to them including basic demographic information, undergraduate CPT teaching, experience of ADR and any deficiency in the under-graduate CPT teaching. Results: Response rate was 91 % in which 53 were males and 47 females. 81 considered themselves aware of CPT. 56% & 57% interns were able to prescribe drug safely and rationally respectively. Without supervision, they were confident to prescribe antacids (93%), vitamins and minerals (90%), NSAIDS (85%), antihistamines (82%), antibiotics (75%), antiemetics (62%) and antiasthmatics (52%). Only 22% had reported ADR and opined that it could lead to hospitalization (51%), prolonged hospital stay (33%), morbidity (16%) and death (21%). According to interns, the topics where more emphasis needed were ADR, dosage calculation, pediatric and emergency medicine and therapeutic drug monitoring during undergraduate CPT teaching. Conclusion: CPT teaching should be improved at undergraduate level for safe and rational prescribing including ADR monitoring, ADR reporting and dosage calculation.